Proyecto de Factibilidad para la Implementación de una Empresa Productora y Comercializadora de Plantas Ornamentales en la Ciudad de Loja - Huanca Tandazo, Jenny Teresa (2016)
Current economic integration trends, changes in buying habits, offer challenges and opportunities for small and medium entrepreneurs. That is why new generations of professionals have to make efforts to create small innovative companies occupying local labor, resources of the town and products that can go to market in optimum conditions and at prices that can compete with other similar products that come from other cities. It is for this reason that the project aims to help with the implementation of a company that allows to create jobs, takes advantage of the natural resources, creating economic value added and thus implement the knowledge acquired for the benefit of a society that needs professional entrepreneurs. Being convenient to carry out and implement the thesis project "Feasibility Project for the production and commercialization of ornamental plants in the city of Loja". To develop this research, it is required the completion of the following studies: Market study, technical study, administrative and legal study, economic and financial study and finally the project evaluation. The market study analyzes the supply and the demand, for which a survey was applied to both applicants and bidders and thus to determine the unsatisfied demand that is 1 476 179, the installed capacity which is 100% and the capacity of the project being 4816 ornamental plants in each production process. The place where the company will be implemented is in the city of Loja, Carigan neighborhood sector Carmelo Av. Padre Solano Km 4 ½ route to Cuenca. Administrative and legal study of the company facilitates determining the business group, mission, vision, objectives, constitution, organization and functions manuals. The company will trade under the name "PARAISO DE LAS FLORES" Cia. Ltda. The financial and economic study provides insight on investment of the project (investment in fixed assets, deferred assets and working capital) funding budgeted investment, cost analysis, breakeven, and analysis of financial statements (losses profit and cash flow). Finally the project evaluation was conducted to determine its suitability for which the following indicators were used: VAN (43561,43), TIR (64,96), RBC (0.34 for every dollar invested), PR (the capital will be recovered over a period of 1 years and 6 months) sensitivity analysis indicates that the project supports an increase in costs of 22,24% giving a total of 0.99% and a decrease in the cost of giving a 16,51% total of 0.99 for which the project is acceptable. At the end the conclusions and recommendations are presented that you arrived at the end of the work, being attached the consulted bibliography with their respective annexes.